ANALISIS PERSEPSI DAN PENGETAHUAN AKUNTANSI PENGGUNA SAK ETAP TERHADAP SAK ENTITAS PRIVAT (EP) PADA PENYUSUNAN LAPORAN KEUANGAN (STUDI EMPIRIS PADA KOPERASI DI KOTA BANJAR, JAWA BARAT) - Suhendar, Endang; Rusmana, Oman; Putri, Negina Kencono (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
The research aims to answer the phenomenon that occurs in the preparation of cooperative financial reports regarding changes in financial accounting standards from SAK ETAP to SAK EP by conducting an in-depth analysis through the Luder contingency model to identify and analyze accounting perceptions and knowledge of SAK EP. It is qualitative research with observation, interviews, and documentation as data collection techniques. The data collection is processed through 3 stages; orientation, exploration, and member check. The results concluded that; Stimuli: standardization of private entity financial reports (SAK EP) was approved by DSAK IAI on 30 June 2021. Producers Information: Explain that there is no information and training regarding changes to financial accounting standards to SAK EP. Implementation Barriers: The lack of literacy in financial accounting standards and the development of accounting guidelines in cooperatives have made cooperatives unaware of the accounting standard guidelines used and those that are currently being developed. The research implications expect the government to plan seminars and training programs so that cooperative human resources can prepare themselves for the change from SAK ETAP to SAK EP which will take effect in 2025.